PENGARUH SOSIAL BUDAYA TERHADAP PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS BATUNADUA KOTA PADANGSIDIMPUAN TAHUN 2015 - Batubara, Novita Sari (Universitas Aufa Royhan, 2016)
Exclusive breast milk is breastfeeding with only breast milk to new-born babies until they aresix months old, without any other food supplement. The coverage of breastfeeding exclusive breastmilk in the working area of Batunadua Health Centre, in 2013, was still low (22.4%). The factor whichis assumed to be the influence on breastfeeding with exclusive breast milk is socio-culture. Theobjective of the research was to analyze the influence of socio-culture on breastfeeding with exclusivebreast milk in the working area of Batunadua Health Centre, in 2015.The research used explanatory research. It was conducted in the working area of BatunaduaHealth Centre, in 2015. The population was 205 women who had 7-12 month old babies, and thesamples were 67 babies, taken by using simple random sampling technique. The data were gathered byconducting interviews and question-naires and analyzed by using univatriate, bivatriate, andmultivatriate analyses with multiple logistic regression analysis.The result of the research showed that the variable of habit had influence on breastfeeding withexclusive breast milk (p = 0.001), while the variable of knowledge did not have any influence onbreastfeeding with exclusive breast milk (p = 0.402) and the variable of confidence also did not haveany influence on breastfeeding with exclusive breast milk (p = 0.80).It is recommended that Padangsidempuan City Administration through the Health Serviceincrease breastfeeding with exclusive ASI program and the role of health care providers, especially those who work at village, socialize the information about the benefit of exclusive breast milk forpregnant and breastfeeding women.